Analisis Efisiensi Biaya Produksi Dalam Penetapan Laba Pada Peternakan Pir Azrul Fani Saragih - Rapat Piter Sony Hutauruk (Accounting Progress, 2025)
This study aims to analyze cost efficiency and profit determination at Pir Azrul Fani Saragih Poultry Farm based on five production cycles. This research employs a descriptive qualitative approach using primary data obtained through interviews and secondary data derived from cost and revenue records for each cycle. The results indicate that total production costs consist of raw material costs, direct labor costs, and overhead, with raw materials being the largest and most volatile component. The cost efficiency analysis shows that the first three cycles achieved efficiency levels below 100%, while the fourth and fifth cycles experienced inefficiency due to actual costs exceeding budgeted amounts. Profit also fluctuated, with the highest value recorded in the second cycle at Rp17,121,776 and the lowest in the fifth cycle at Rp5,631,332. These findings demonstrate that profit is strongly influenced by a combination of selling price variations and the effectiveness of cost control. The study concludes that cost control has not been consistently implemented, indicating the need for standard costing and more systematic cost evaluation to enhance business profitability.